Operator dependent factors implicated in failure of non‐invasive positive pressure ventilation (NIPPV) for respiratory failure. (6th January 2016) - Bhatti, Hammad; Ramdass, Avinash; Cury, James D.; Jones, Lisa M.; Shujaat, Adil; Louis, Mariam; Seeram, Vandana; Bajwa, Abubakr A.
Abstract: Background: Non‐invasive Positive Pressure Ventilation (NIPPV) is employed for the management of acute respiratory failure and studies have shown that it can prevent the need for endotracheal intubation, mechanical ventilation and associated complications. Given limited studies evaluating the factors, other than those related patient or underlying disease severity, that may lead to NIPPV failure, we performed this study to gain insight into current practices in terms of utilization of NIPPV and operator dependent factors that may possibly contribute to failure of NIPPV. Method: After institutional board review approval a retrospective chart review was performed of consecutive patients who were initiated on and failed NIPPV between January 2009 and December 2009. Data was recorded regarding baseline demographics, admission diagnosis, indications for NIPPV, presence of contraindications, type of NIPPV and initial settings, ABG analysis before and after initiation, whether a titration of the settings was performed or not, operator related factors that may have contributed to failure of NIPPV and clinical outcomes. Results: Among 1095 patients screened, 111 failed NIPPV. The mean age was 60 years with 59% males. The most frequent indication for initiating NIPPV was COPD exacerbation ( N = 27) followed by pneumonia ( N = 26). CPAP was used in 5(6%) patients. Median inspiratory positive airway pressure (IPAP) and expiratory positive airway pressure (EPAP) setting were 10 and 5 cm of H2 O respectively. Three most common reasons for failure were an inappropriate indication (33%), Progression of underlying disease (30%) and lack of titration (23%). Overall mortality was 22%. Mortality was higher when NIPPV failure was seen among patients with an inappropriate indication or an overlooked contraindication compared to those with an appropriate indication (27% vs 17%). Conclusions: Excluding progression of underlying disease, operator dependent factors linked to NIPPV failure are; inappropriate indication, lack of adequate titration and an overlooked contraindication. Inappropriate utilization of NIPPV in respiratory failure is associated with higher mortality.